Quantitative high-throughput analysis of tumor infiltrating lymphocytes in breast cancer - Hayashi, Kumiko; Nogawa, Daichi; Kobayashi, Maki; Asakawa, Ayaka; Ohata, Yae; Kitagawa, Shota; Kubota, Kazuishi; Takahashi, Hisashi; Yamada, Miyuki; Oda, Goshi; Nakagawa, Tsuyoshi; Uetake, Hiroyuki; et al. (Frontiers in Oncology, 2022)
In breast cancer (BC), the development of cancer immunotherapy including immune checkpoint inhibitors has progressed. Tumor infiltrating lymphocytes (TILs) is one of the important factors for an immune response between tumor cells and immune cells in the tumor microenvironment, and the presence of TILs has been identified as predictors of response to chemotherapy. However, because complex mechanisms underlies the crosstalk between immune cells and cancer cells, the relationship between immune profiles in the tumor microenvironment and the efficacy of the immune checkpoint blocked has been unclear. Moreover, in many cases of breast cancer, the quantitative analysis of TILs and immuno-modification markers in a single tissue section are not studied. Therefore, we quantified detailed subsets of tumor infiltrating lymphocytes (TILs) from BC tissues and compared among BC subtypes. The TILs of BC tissues from 86 patients were classified using multiplex immunohistochemistry and an artificial intelligence-based analysis system based on T-cell subset markers, immunomodification markers, and the localization of TILs. The levels of CD4/PD1 and CD8/PD1 double-positive stromal TILs were significantly lower in the HER2- BC subtype (p <0.01 and p <0.05, respectively). In triple-negative breast cancer (TNBC), single marker-positive intratumoral TILs did not affect prognosis, however CD4/PDL1, CD8/PD1, and CD8/PDL1 double-positive TILs were significantly associated with TNBC recurrence (p<0.05, p<0.01, and p<0.001, respectively). TIL profiles differed among different BC subtypes, suggesting that the localization of TILs and their tumor-specific subsets influence the BC microenvironment.